(untitled) (Comprehensive Journal of Science, 2025)
This research examines the concept of preventive diplomacy, highlighting the diversity within this concept. It also addresses the objectives of preventive diplomacy, noting the mechanisms, methods, and manifestations of preventive diplomacy. It also explains the nature of a UN envoy and the criteria upon which such a particular envoy should be appointed. The problem of this research revolves around the central question of what is the concept of preventive diplomacy and whether it is effective these days in confronting these successive events. The research is important in that preventive diplomacy works to reduce tensions affecting international relations, which may lead to war, thus impacting international situations. It aims to reduce conflicts that occur between countries, affecting the international community as well as international peace and security. We have reached some conclusions, including that preventive diplomacy plays a role in reducing international conflicts and disputes, whether within a country or between countries. We recommend further research to demonstrate the benefits of preventive diplomacy.